Home care experiences of mothers of children with tracheostomies – a qualitative study - Donmez, Hatice; Gozetici, Elif (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Parents of children who are addicted to technology have many problems in home care. This study aimed to describe the home care experiences of mothers of children with tracheostomies. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The study adopted Husserl’s phenomenological method, a qualitative research design. The sample consisted of 23 mothers of children with tracheostomies followed up in the pediatric pulmonology outpatient clinic of a university hospital. All participants cared for their children at home. Data were collected using a sociodemographic questionnaire and a semi-structured interview questionnaire. All interviews were recorded and transcribed. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Children (12 girls and 11 boys) had a mean age of 3.43±3.326 years. The mean age of tracheostomy insertion was 2.8±2.508 years. Seventeen children were on ventilator support. All participants were mothers with a mean age of 32.34±6.00 years. Half the mothers had primary school degrees (52.2%). The interviews revealed one main theme (burnout), three subthemes (social isolation, perception of competence, and regrets), and five categories (burden of care, fear, awareness, decisions, and role confusion). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Mothers of children with tracheostomies experience numerous problems when they provide home care. They mostly have difficulty improving themselves and enduring role confusion. We must address the issues mothers of children with tracheostomies face during home care to reduce the prevalence of potential complications and improve the quality of care for both them and their children.